Systolic Pressure, not the Diastolic Pressure Expresses Better the Relationship between Age and Blood Pressure Changes in a Community Sample of Adults - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Hypertension is an important cause of the cardiovascular disease (CVD). Blood pressure (BP) elevations and the associated complications are influenced by age.Aim:To evaluate age-related variations in systolic BP, diastolic BP, and the derived pulse pressure (PP), mean arterial pressure (MAP), as well as pulse rate (PR) in a community sample of adults in Sokoto.Settings and Design:Adult individuals, predominantly non-hypertensive, non-diabetic that attended a free medical screening in a Sokoto community, Northwestern Nigeria were evaluated.Materials and Methods:Blood pressure, anthropometry, and random blood glucose were measured.Statistical Analysis Used:Database storage and analysis were carried out using IBM SPSS, version 23.0.Results:Systolic BP correlates with age increases beyond other BP parameters (standardized β-coefficient of systolic BP = 0.4071, R2= 0.0933, Diastolic BP = 0.1485, R2= 0.0409, PP = 0.2587, R2= 0.0661, MAP = 0.2347, R2= 0.0757, PR = -0.0087, R2= 0.0001). The same trend was observed when age-dependent variations in the BP parameters were assessed independent of body weights (Fcrit = 2.398, F = 151.911, df = 4,P= 0.000) and independent of the steady state pressure, MAP (Fcrit = 2.637, F = 795.975,P= 0.000). However, when the population is considered by age categories of ≤50 years or >50 years separately, diastolic BP rather than the systolic BP better explain the relationship in the ≤50 years category.Conclusion:Although all the components of BP should be monitored when treating hypertension in adults, systolic BP and its derivative PP be given more attention.